2018
DOI: 10.1075/hl.00018.mce
|View full text |Cite
|
Sign up to set email alerts
|

August Schleicher and Materialism in 19th-Century Linguistics

Abstract: Towards the end of his career, August Schleicher (1821–1868), the great consolidator of Indo-European historical-comparative linguistics in the mid-19th century, famously drew explicit parallels between linguistics and the new evolutionary theory of Darwinism. Based on this, it has become customary in linguistic historiography to refer to Schleicher’s ‘Darwinian’ theory of language, even though it has long been established that Schleicher’s views have other origins that pre-date his contact with Darwinism. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…In a linguistic sense, it was first introduced in 1859 by the German linguist A. Schleicher, claiming: "for the science of word formation, I choose the term 'morphology'" (Szemerényi, 1996). His goal was to create a synchronous description of forms in languages without taking into account their historical development (McElvenny, 2018). In Ukrainian, the word is borrowed from German -Morphologie (Etymological era, 1989).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a linguistic sense, it was first introduced in 1859 by the German linguist A. Schleicher, claiming: "for the science of word formation, I choose the term 'morphology'" (Szemerényi, 1996). His goal was to create a synchronous description of forms in languages without taking into account their historical development (McElvenny, 2018). In Ukrainian, the word is borrowed from German -Morphologie (Etymological era, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical basis of the study were works on the formation and development of morphology as a general scientific doctrine in the philosophical worldview (Aristotle, 1976;Kanaev, 1970;Mikulinsky, ed., 1972;Reshetov and Stezhko, 2013;Tararoev, 2009;Shcherba et al, 2004;) and logical-epistemological (Bakhtin, 1987;Biskub, 2014;Dika, 1975;Etymological…, 1982Etymological…, -2012Mala…, 2004Mala…, -2013Dictionary…, 1970Dictionary…, -1980Yudkin-Ripun, 2006;2011;) contexts. Works on the specifics of the functioning of morphology in biology (Meyer, 1958;Meyen, 2010;Lutz, 2002;McLaughlin, 2002), philology (McElvenny, 2018;Szemerényi, 1996), geology (Biletsky, 2007) and geography have become particularly important (Huggett, 2007;Simonov, 2005). A sample analysis of theoretical and methodological foundations related to the study of morphology at a specific scientific level and identified features of the use of specialized terminology (Timonin, 2001).…”
Section: Analysis Of Research and Publicationsmentioning
confidence: 99%
“…DeGraff ( 2001), for one, applies this label to Schleicher's thought and work he sees following in its footsteps, including McWhorter (2001). While it is true that Schleicher, toward the end of his career, attempted to align his work with Darwinian doctrine (most notably in Schleicher, 1863), his proposals for morphology predate this connection and were in fact not entirely compatible with Darwin's views (see Alter, 1999;McElvenny, 2018a). 4 Schleicher's thought was more directly influenced by idealist Naturphilosophie, in particular the theory of plant and animal "morphology" advanced by Johann Wolfgang von Goethe (1749-1832), which was later taken up and developed further in a "monist" mode by Ernst Haeckel (1834-1919see Richards, 2008, Appendix 1).…”
Section: Linguistic Perfectionmentioning
confidence: 99%
“…Por un lado, Schleicher tomó la decisión de trabajar con un poema cuya autoría se suele asignar a un relato oral cristalizado, como parte de una representación de palabras que se presuponen ampliamente difundidas; en segundo lugar, se trata del poema más importante de la cultura alemana, reconocido ya en el siglo XIX como una de las bases de la identidad de lo que hasta entonces no se había conformado como una nación unificada en un Estado común (Cipolla, 2018). Y es precisamente en torno a la utilización del poema de los Nibelungos que desarrolla, en el prefacio de su obra más política, Die deutsche Sprache (McElvenny, 2018), la explicación para la elaboración de su teoría. Según Schleicher, una teoría sobre la evolución del lenguaje le permitiría a un sector más amplio de la población alemana comprender el alto germánico antiguo y por ello el origen del alemán moderno:…”
Section: Todo Menos Predicadorunclassified